People play it down and tell me it can't kill people, but i know people are dying each day. Children's health literacy relating to a global pandemic (COVID-19); An international cross sectional study - Bray, Lucy; Carter, Bernie; Blake, Lucy; Saron, Holly; Kirton, Jennifer A.; Robichaud, Fanny; Avila, Marla [UNESP]; Ford, Karen; Nafria, Begonya; Forsner, Maria; Nilsson, Stefan; Chelkowski, Andrea; et al. (Public Library of Science (PLoS), 2021)
The aim of this study was to examine aspects of children's health literacy; the information sources they were accessing, their information preferences, their perceived understanding of and their reported information needs in relation to COVID-19. An online survey for children aged 7-12 years of age and parent/caregivers from the UK, Sweden, Brazil, Spain, Canada and Australia was conducted between 6th of April and the 1st of June 2020. The surveys included demographic questions and both closed and open questions focussing on access to and understanding of COVID-19 information. Descriptive statistics and qualitative content analysis procedures were conducted. The findings show that parents are the main source of information for children during the pandemic in most countries (89%, n = 347), except in Sweden where school was the main source of information. However, in many cases parents chose to shield, filter or adapt their child's access to information about COVID-19, especially in relation to the death rates within each country. Despite this, children in this study reported knowing that COVID-19 was deadly and spreads quickly. This paper argues for a community rather than individual approach to addressing children's health literacy needs during a pandemic.